Moral panics - Thompson, Kenneth, 1937- (Key ideas., 2005)
With the increasing number of moral panics in recent years triggered by incidents such as the Bulger case and the spread of AIDS, this book examines their wider significance particularly in terms of the functioning of the mass media.